Korelasi antara Sikap Terhadap Perbedaan Kultur dan Intensi Turnover pada Karyawan Perusahaan X - Fabrikasi, Tiara; Prasetya, Berta Esti Ari (Psychopreneur Journal, 2021)
This study aims to determine the correlation between attitudes toward cultural differences with turnover intention in employees company X. the hypothesis in this study there is significant negative relation between attitudes toward cultural differences and turnover intention in employees company X. the subject in this studying were 55 employees from company X. The data obtained using aattitudes toward cultural difference scale and a scale of turnover intention. The result showed a value of ρ =-0.738 with p = 0.000 (p<0.05). Thus, it can be concluded that there is a significant negative correlation between attitudes toward cultural differences and turnover intention in employee company X. So, the hypothesis proposed in this study can be accepted.